An assessment of the welfare of non-human primates used in neuroscience research - Heppenstall, R (2023)
The Animals (Scientific Procedures) Act 1986 governs the use of animals in scientific research in the UK. Embedded within this is a requirement to implement the 3Rs: replacement, reduction, and refinement; a key mechanism for minimising the pain, suffering, distress, and lasting harm of research models. To adhere fully to these principles, it is imperative to assess animal welfare. Non-human primates (NHP) human similarities make them both an essential biomedical research model and a species particularly vulnerable to welfare challenges. This thesis investigates non-invasive, objective methods of welfare assessment and applies them alongside neuroscience research to monitor the welfare of rhesus macaques (Macaca mulatta).